1998
DOI: 10.1095/biolreprod59.3.606
|View full text |Cite
|
Sign up to set email alerts
|

Time-Course of the Uterine Response to Estradiol-17β in Ovariectomized Ewes: Uterine Growth and Microvascular Development1

Abstract: The time-course of uterine growth, cell proliferation, and microvascular development was evaluated during the first 72 h after implanting estradiol-17beta (E2) into ovariectomized (OVX) ewes. Uterine fresh weight increased 2.3-fold by 24 h and increased further (3.3-fold) by 48 h. The majority (approximately 75%) of this growth response was associated with tissue growth rather than a change in the tissue dry weight:fresh weight ratio. Both uterine cell number (DNA content) and cell size (RNA:DNA ratio) increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
1
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 24 publications
3
58
1
1
Order By: Relevance
“…Figure 2 Representative micrographs of vascular perfused cotyledonary tissue at day 50 of gestation in control (A) and high (B) dietary-intake groups. The pinkish staining (periodic acid-Schiff's reagent) represents primarily basement membranes, including those of the microvessels (capillaries, arterioles, and venules; Borowicz et al 2007), the brown nuclei indicate the presence of BrdU and therefore marks DNA synthesis and thus cell proliferation (Johnson et al 1997a, Reynolds et al 1998, and the bluish nuclei represent non-proliferating nuclei counterstained stained with hematoxylin. Cotyledonary capillary area density (capillary area per unit of cotyledonary tissue) and number density (number of capillaries per unit of cotyledonary tissue) were reduced by 46 and 51% respectively in the high (B) versus the control (A) dietary groups at day 50 of gestation (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2 Representative micrographs of vascular perfused cotyledonary tissue at day 50 of gestation in control (A) and high (B) dietary-intake groups. The pinkish staining (periodic acid-Schiff's reagent) represents primarily basement membranes, including those of the microvessels (capillaries, arterioles, and venules; Borowicz et al 2007), the brown nuclei indicate the presence of BrdU and therefore marks DNA synthesis and thus cell proliferation (Johnson et al 1997a, Reynolds et al 1998, and the bluish nuclei represent non-proliferating nuclei counterstained stained with hematoxylin. Cotyledonary capillary area density (capillary area per unit of cotyledonary tissue) and number density (number of capillaries per unit of cotyledonary tissue) were reduced by 46 and 51% respectively in the high (B) versus the control (A) dietary groups at day 50 of gestation (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…However, we have recently shown that circulating oestradiol-17b concentrations in identically nutritionally manipulated overnourished dams fail to increase in parallel with those of control dams between day 50 and 75 of gestation (Wallace et al 2008b). The reproductive steroids are strongly implicated in the control of uterine growth (Johnson et al 1997a, Reynolds et al 1998 Alternatively, nutritionally-mediated alterations in placental angiogenesis and vascular development may reflect differences in circulating somatotrophic hormones. Insulin and, to a lesser extent, IGF1 concentrations are elevated from early in gestation in overnourished dams and provide a sustained anabolic stimulus to maternal tissue deposition (Wallace et al 1997a, present study).…”
Section: Discussionmentioning
confidence: 99%
“…The reason why PKC is not involved in PDGF-induced VEGF production in HUSMCs is unclear, but our experiment indicates that PDGF raises VEGF secretion predominantly through MAPK activation. Reynolds et al (1998) reported that 17 -estradiol enhanced VEGF mRNA expression in ovariectomized ewes in vivo. Therefore, to confirm this phenomenon, HUSMCs were treated with 17 -estradiol, and VEGF protein levels in the medium were measured.…”
Section: Discussionmentioning
confidence: 98%
“…The stimulatory effect of PDGF on cell proliferation was confirmed by the increase in cell number (control: 42·2 0·9 10 3 /well; PDGF: 56·3 2·3 10 3 /well). Because myometrial smooth muscle in ewes showed immunostaining for VEGF (Reynolds et al 1998), we investigated whether PDGF affected VEGF secretion from HUSMCs. We measured the content of VEGF in cultured media from cells after incubation for 24 h in serum-free DMEM with various doses of PDGF.…”
Section: Effect Of Pdgf On Husmc Proliferation and Vegf Production Inmentioning
confidence: 99%
“…Além disso, em ovelhas intactas, a proliferação celular no epitélio luminal, glândulas superficiais, glândulas profundas, estroma subepitelial superficial e profundo foi superior durante o estro em relação à fase luteal (JOHNSON et al, 1997a,b). Estudos em ovelhas intactas (JOHNSON et al, 1997a,b) e ovelhas ovariectomizadas tratadas com E2 exógeno (REYNOLDS et al, 1998) 58.0%; FG: 57.3%; PRO: 63.4%) than cows from the other groups (P < 0.05). Cows from…”
Section: Efeitos Dos Esteróides Ovarianos Na Morfologia Uterinaunclassified